Bidirectional User Throughput Maximization Based on Feedback Reduction in LiFi Networks - Soltani, Mohammad Dehghani; Xiping Wu; Safari, Majid; Haas, Harald (IEEE transactions on communications, 2018)
Channel adaptive signaling, which is based on feedback, can result in almost any performance metric enhancement. Unlike the radio frequency channel, the optical wireless communication (OWC) channel is relatively deterministic. This feature of OWC channels enables a potential improvement of the bidirectional user throughput by reducing the amount of feedback. Light-Fidelity (LiFi) is a subset of OWCs, and it is a bidirectional, high-speed, and fully networked wireless communication technology where visible light and infrared are used in downlink and uplink, respectively. In this paper, two techniques for reducing the amount of feedback in LiFi cellular networks are proposed: 1) limited-content feedback scheme based on reducing the content of feedback information and 2) limited-frequency feedback scheme based on the update interval. Furthermore, based on the random waypoint mobility model, the optimum update interval, which provides maximum bidirectional user equipment throughput, has been derived. Results show that the proposed schemes can achieve better average overall throughput compared with the benchmark one-bit feedback and full-feedback mechanisms.